2018
DOI: 10.1557/mrs.2018.181
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free piezoceramics: Status and perspectives

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
77
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(77 citation statements)
references
References 93 publications
0
77
0
Order By: Relevance
“…In 2004, Saito et al demonstrated that alkali niobate (K 0.5 Na 0.5 NbO 3 , KNN)-based ceramics exhibit piezoelectric properties comparable to the market-dominant lead zirconate titanate (PZT) [1]. Since then, considerable effort, fueled by worldwide regulations restricting the use of lead in electronic devices [2], has been devoted to further improve the piezoelectric properties of KNN-based solid solutions, now considered among the most promising lead-free piezoceramics [3].…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Saito et al demonstrated that alkali niobate (K 0.5 Na 0.5 NbO 3 , KNN)-based ceramics exhibit piezoelectric properties comparable to the market-dominant lead zirconate titanate (PZT) [1]. Since then, considerable effort, fueled by worldwide regulations restricting the use of lead in electronic devices [2], has been devoted to further improve the piezoelectric properties of KNN-based solid solutions, now considered among the most promising lead-free piezoceramics [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among these lead‐free piezoelectrics, KNN‐based ceramics have made great progress and achieved significant breakthroughs in the past 20 years, since a high d 33 (≈416 pC N −1 ) in (K,Na,Li)(Nb,Ta,Sb)O 3 ‐textured ceramics was reported by Satio et al. and eventually demonstrated large d 33 and high T C . In the meantime, KNN‐based ceramics have been considered to possess the closest characteristics with respect to PZT .…”
Section: Introductionmentioning
confidence: 99%
“…(See Table 1 .) In particular, recent legislation, the “Restriction of Hazardous Substances”, strictly limits the use of specific hazardous materials found in electrical and electronic products, which orient the research scope of electronic device and materials toward Pb‐free electronics . Hence, utilizing non‐toxic earth‐abundant substances for high‐performance and low‐power electronics must be a genuine and desirable research path for the sustainable future.…”
Section: Introductionmentioning
confidence: 99%